An experimental investigation of rating-market regulation - Claudia Keser; Asri Özgümüs; Emmanuel Peterlé; Martin Schmidt (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
We introduce a simple game-theoretical model that captures the main aspects of the repeated interaction between an issuer and a credit-rating agency. It involves up-front payments of issuer-fees and direct publication of requested ratings. Due to pecuniary injuries for untruthful ratings, the creditrating agency should always report truthfully in the subgame perfect equilibrium. Knowing this, the issuer should never request a rating. Conducting laboratory experiments, we find that behavior significantly deviates from the equilibrium prediction in favor of a cooperative solution: issuers frequently do request ratings, which is often reciprocated with untruthful good ratings.
Keywords: C70; C9; G0; 330; game theory; laboratory experiments; rating agencies; regulation